Characterization of complete mitochondrial genome of Aphyocypris pulchrilineata (Teleostei, Cypriniformes, Cyprinidae). Issue 1 (2nd January 2019) - Luo, Fuguang; Luo, Tong; Huang, Jie; Liu, Xia; Situ, Ling; Wen, Yanhong
Abstract: Aphyocypris pulchrilineata is a miniature cyprinid fish that only found in the streams or the underground river outlet of Hongshui River and Liujiang River, Southwestern China. The complete mitochondrial genome is 16, 610 bp in length, consisting of 37 genes coding for 13 proteins, two rRNAs, 22 tRNAs, and one control region with 936 bp long. Phylogenetic analysis using mitochondrial genomes of 16 species showed that the genus Aphyocypris, Yaoshanicus, Pararasbora, and Nicholsicypris clustered as a monophyletic clade with strong supports, and A. pulchrilineata was the most basal species in this clade.